Routledge handbook of graffiti and street art - Ross, Jeffrey Ian (Routledge, 2016)
pt. I: History, types, and writers/artists of graffiti and street art -- pt. II: Theoretical explanations of graffiti and street art/causes of graffiti and street art -- pt. III: Regional/municipal variations/differences of graffiti and street art -- pt. IV: Effects of graffiti and street art.